Preservation in New Buildings - Kitching, Christopher (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
In the United Kingdom (as in many other countries) increasing attention is being paid to the importance of each library and archive having a written preservation strategy endorsed by its governing body. So increasingly we are asking: where does „preservation“ begin and what are its top priorities? Some would say preservation begins with the definition of collecting policies to ensure that only relevant items are acquired in the first place, and therefore that no unnecessary costs are incurred on the long-term care of unwanted and unconsulted items. Others might argue that the first priority must be the careful appraisal of existing holdings to determine their preservation and conservation requirements and to prioritise their treatment. Or should preservation begin with damage-limitation: restricting the physical handling of books and documents, on the one hand by providing whenever possible surrogate copies in digital formats or microform, and on the other hand by offering at least basic protection through appropriate boxing and packaging? This, surely, goes hand-in-hand with the education of staff and readers about the importance of treating rare or unique materials with proper respect.